Relationships among work-family conflict, organizational silence, peer support, and turnover intention of second child nurses in China - Huang Xiaoqiong (2021)
This empirical study is based on a survey among Chinese nurses. Nurses in 216 secondary and tertiary level hospitals were selected using convenience sampling method, and 3,974 valid questionnaires were obtained. Four scales were adopted: Work-Family Conflict Scale, Organizational Silence Scale, Peer Support Scale and Turnover Intention Scale. IBM SPSS Statistics and AMOS were used. The results showed that the work-family conflict, organizational silence and peer support of Chinese nurses were all at medium to high levels. Nurses without children had lower levels of work-family conflict than nurses with a child or children; nurses with one child had lower levels of work-family conflict than nurses with two or more children; compared with nurses without children, nurses with a child or children had lower levels of turnover intention; work-family conflict positively influenced turnover intention; peer support negatively influenced organizational silence and turnover intention; organizational silence positively influenced turnover intention. Work-family conflict and peer support had both direct and indirect effects on turnover intention; organizational silence had a direct effect on turnover intention; and peer support and organizational silence mediated the relationship between work-family conflict and turnover intention. This study explored the formulation of motivational management strategies. The factors influencing nurses' turnover intention and the relationships among them were discussed. The results showed that the number of children influences nurses' work-family conflict, organizational silence, peer support, and turnover intention. This study provides insights for nursing managers to improve nursing management models and health policies.